2004
DOI: 10.1074/jbc.m308281200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phosphorylation in D1 Dopamine Receptor Desensitization

Abstract: Homologous desensitization of D 1 dopamine receptors is thought to occur through their phosphorylation leading to arrestin association which interdicts G protein coupling. In order to identify the relevant domains of receptor phosphorylation, and to determine how this leads to arrestin association, we created a series of mutated D 1 receptor constructs. In one mutant, all of the serine/threonine residues within the 3rd cytoplasmic domain were altered (3rdTOT). A second construct was created in which only three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 32 publications
7
64
0
Order By: Relevance
“…The specificity of this recycling defect is consistent with previous studies indicating that similar (or even more extensive) truncations of the D1 cytoplasmic tail do not disrupt ligand binding, G protein coupling, or rapid desensitization of receptors (10,25,26). Previous studies have identified a sequence in the proximal cytoplasmic tail of the D1 receptor that (by interacting with the cytoplasmic protein DRIP78) promotes export of newly synthesized receptors from the endoplasmic reticulum (32).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The specificity of this recycling defect is consistent with previous studies indicating that similar (or even more extensive) truncations of the D1 cytoplasmic tail do not disrupt ligand binding, G protein coupling, or rapid desensitization of receptors (10,25,26). Previous studies have identified a sequence in the proximal cytoplasmic tail of the D1 receptor that (by interacting with the cytoplasmic protein DRIP78) promotes export of newly synthesized receptors from the endoplasmic reticulum (32).…”
Section: Discussionsupporting
confidence: 77%
“…2A). Whereas previous work has shown that truncations near this region of the D1 receptor typically result in diminished amounts of surface receptor expression (25,26), cell clones used to compare trafficking of wild-type and mutant receptor constructs expressed the indicated receptors within a closely similar (ϳ3-fold) range. Furthermore, reduced recycling of the HA-D1-359T mutant receptor was observed in multiple independently isolated cell clones differing in mutant receptor expression by ϳ5-fold (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, phosphorylation of the 5-HT 4 R C-terminal domain seems to be absolutely necessary for ␤-arrestin recruitment. This model contrasts with those of the dopamine D 1 receptor, in which phosphorylation of Ser/Thr permits access of arrestin to its receptor-binding domain rather than creating an arrestin-binding site per se (28). However, in our study, the ⌬346 mutant, whose i 3 loop is easily accessible, did not associate with ␤-arrestin, whereas the ⌬358 mutant, which possesses the Ser/Thr cluster, was always able to interact with ␤-arrestin.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, recent evidence has accumulated for a number of GPCRs suggesting that receptor phosphorylation is not always required for their desensitization or internalization (12)(13)(14)(15)(16)(17). This appears to be particularly true for G q/11 -linked GPCRs, which can be regulated by GRK2-mediated mechanisms that are independent of receptor phosphorylation.…”
Section: Dopamine Receptors (Dars)mentioning
confidence: 99%